Efektivitas Model Pembelajaran Terhadap Hasil Belajar Siswa Kelas XI pada Materi Laju Reaki - Desti, Desti; Esnawi, Esnawi; Maysara, Maysara (Chemistry Education Practice, 2025)
Research has been conducted on the effectiveness of Problem Based Learning model on the learning outcomes of Class XI students of SMAN 3 Sampolawa on reaction rate material. This study aims to determine the effectiveness of Problem Based Learning model on student learning outcomes on reaction rate material. The subjects in this study were 25 students of class XI MIPA 1. This type of research is pre-experiment with One Group Pretest-Posttest design. The research instruments included a learning outcome test consisting of 20 multiple choice questions and an observation sheet. The results showed that the average pretest score of 29.6 increased to 77.2 in the posttest. The effectiveness of learning based on the N-Gain value of 0.68 is included in the medium category, so the Problem Based Learning model is declared effective in improving student learning outcomes. Students' responses to the learning model were classified as very good, while the implementation of learning by teachers and students was considered good and experienced an increase. Keywords: Effectiveness, Problem Based Learning, Learning Outcomes, Reaction Rate